The Effect of Problem-Based Learning on Improving the Ability to Find Alternative Solutions Through Group and Independent Work - Suharsono, Naswan; Rachmad Hidayat; Iva Khoril Mala; Imam Buchori (International Journal of Technology and Education Research, 2025)
The implementation of the ‘Freedom to Learn Curriculum’ in higher education can serve as a catalyst for the nation’s future advancement, yet how to realize this potential remains a critical question. This study implements an integrated Problem-Based Learning (PBL) model to enhance students’ ability to solve economic and business problems across time. The research integrates several stages: identifying root problems, theoretical and applied reviews, analyzing government policies in practice, assessing impacts, and developing future problem-solving programs. This research aims to examine the effect of the problem-solving learning model on improving students’ ability to address economic problems, focusing on strengthening self-identity and enhancing both group and individual work abilities. The research design employed a pre-experimental approach, starting with problem identification, theoretical foundation development, field exploration, analysis of supporting policies, and identification of potential impacts for the future. The subjects were 118 students enrolled in the Introduction to Economic Theory course at the Faculty of Economics and Business, Universitas Negeri Malang. Data on improvements in problem-solving ability, operational skills, individual work changes, and teamwork-based problem-solving capabilities were processed using SPSS-23 through ANCOVA with regression analysis. Meanwhile, improvements in problem management and opportunity recognition in economic activities were analyzed using SWOT through group work mechanisms. The process emphasized optimizing accessibility to problem-based activities and varying fieldwork and practical exercises for managing progressive life challenges. The results showed that based on the ANCOVA statistical analysis, the Problem-Based Learning (PBL) model had a significant effect on students’ ability to develop alternative solutions, particularly through teamwork. In the Tests of Between-Subjects Effects model involving two independent variables—CVMT (PBL-based treatment) and TI (individual task category)—the overall model was significant, with a Sig. value of 0.008. This indicates that the combination of PBL treatment and variations in individual assignments jointly influenced students’ group task outcomes. The individual task variable (TI) significantly affected group performance with a significance value of 0.049 and a Partial Eta Squared value of 0.137, indicating a moderate contribution. This means that the type or quality of individual tasks completed by students has a tangible impact on group work success. Descriptive Statistics results showed that the highest average group task scores came from students with individual task categories at scores of 85 (mean = 86.21) and 88 (mean = 86.00), indicating that students with strong individual performance tended to demonstrate better group outcomes. Conversely, groups with lower individual scores (TI = 75) also had lower group performance (mean = 74.65). This supports the assumption that success in group work originates from solid individual contributions. From the Parameter Estimates results, a significant difference was specifically found between the TI = 75 group and the reference group (TI = 90) with p = 0.032, showing that students with lower individual performance exhibited a statistically significant difference in group outcomes